Realigning Health Systems Strategies and Approaches; What Should African Countries Do to Strengthen Health Systems for the Sustainable Development Goals? - Sunny Ibeneme; Moses Ongom; Nkiruka Ukor; Joseph Okeibunor (Frontiers Media S.A., 2020)
The African region is experiencing peculiar demographic, economic, social and environmental challenges that place pressures on the health systems. While the need to explore ways to address identified health systems challenges is far from easy, there are substantial evidence that having robust frameworks and metrics to direct efforts and priorities of countries could be rewarding. In view of persisting regional health systems' challenges the World Health Organization African regional office proposed the adoption of a comprehensive health system strengthening action framework that provides an opportunity to translate global health policy into operational strategies for Africa's health sector policies, strategies and operations. The adoption of the action framework could support the realization of regional health objectives and priorities, and guide movement toward sustainable developments in countries.